Impact of North American intense fires on aerosol optical properties measured over the European Arctic in July 2015. Issue 24 (17th December 2016) - Markowicz, K. M.; Pakszys, P.; Ritter, C.; Zielinski, T.; Udisti, R.; Cappelletti, D.; Mazzola, M.; Shiobara, M.; Xian, P.; Zawadzka, O.; Lisok, J.; Petelski, T.; et al.
Abstract: In this paper impact of intensive biomass burning (BB) in North America in July 2015, on aerosol optical and microphysical properties measured in the European Arctic, is discussed. This study was made within the framework of the Impact of Absorbing aerosols on Radiating forcing in the European Arctic project. During the BB event aerosol optical depth (AOD) at 500 nm exceeded 1.2 in Spitsbergen and 0.7 in Andenes (Norway). Angstrom exponent exceeded 1.4, while the absorbing Angstrom exponent varied between 1 and 1.25. BB aerosols were observed in humid atmosphere with a total water vapor column between 2 and 2.5 cm. In such conditions aerosols are activated and may produce clouds at different altitudes. Vertical structure of aerosol plumes over Svalbard, obtained from ceilometers and lidars, shows variability of range‐corrected signal between surface and middle and upper troposphere. Aerosol backscattering coefficients show values up to 10 −5  m −1  sr −1 at 532 nm. Aerosol surface observations indicate chemical composition typical for biomass burning particles and very high single scattering properties. Scattering and absorption coefficients at 530 nm were up to 130 and 15 Mm −1, respectively. Single scattering albedo at the surface varied from 0.9 to 0.94. The averaged values over the entire atmospheric column ranged from 0.93 to 0.99. Preliminary statistics of model and Sun photometer data as well as previous studies indicate that this event, in the Arctic region, must be considered extreme (such AOD was not observed in Svalbard since 2005) with a significant impact on energy budget. Key Points: Extreme air pollution in the European Arctic studied in summer 2015 Biomass burning event in Northern Canada led to aerosol optical depth of more than 1 at 500 nm This biomass burning in the Arctic region had significant impact on the energy budget